2022
DOI: 10.35633/inmateh-68-75
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research Regarding the Achievement of an Equipment Designed for Chopping Woody Waste

Abstract: This article presents the results obtained through experimental research carried out with a machine for shredding woody plant residues (twigs, vine ropes), residues obtained from dry or green cuttings, in fruit or wine plantations. The obtained shredding is intended for utilization in the form of compost or biofuel (pellet type). The machine was designed and made by a group of researchers from INMA Bucharest, with the aim of developing the machine system made available to farmers, for mechanized work in small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Table 3 presents the average values obtained on these measurements for the theoretical chopping length of 20 mm and 26.8 mm, respectively, for lucerne / vetch crops. Doing a comparative analysis of the dimensions of chopped lucerne and vetch materials with the dimensions of the corn silage presented in paper [5], it is found that for a theoretical adjustment on the drum of 26.8 mm, the particles with the length up to 30 mm represent 60.42 % for lucerne / vetch, with 1.02 % more than in corn silage where 59.4 % was obtained. Also, the percentage of losses for particles exceeding a lenth of 100 mm is in the same range, arround 1.3 %…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…Table 3 presents the average values obtained on these measurements for the theoretical chopping length of 20 mm and 26.8 mm, respectively, for lucerne / vetch crops. Doing a comparative analysis of the dimensions of chopped lucerne and vetch materials with the dimensions of the corn silage presented in paper [5], it is found that for a theoretical adjustment on the drum of 26.8 mm, the particles with the length up to 30 mm represent 60.42 % for lucerne / vetch, with 1.02 % more than in corn silage where 59.4 % was obtained. Also, the percentage of losses for particles exceeding a lenth of 100 mm is in the same range, arround 1.3 %…”
Section: Resultsmentioning
confidence: 94%
“…According to the authors [5], during the experiments under laboratory conditions, the cascading knife chopping drum achieved higher indices (lower driving power, higher airflow velocity) than those with "V" placed knives with or without blades.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spinelli and Picchi, (2010), confirmed that the potential supply of wood from orchards ranged from 0.6 to 20 million m 3 /year. For many years, most growers have treated the apple branch pruning residues by either stacking them together and burning them, or directly smashing them by a shredder to cover the soil (Popa et al, 2022). Obviously, these methods do not bring economic benefits to growers and may pollute air quality and the environment.…”
Section: Introductionmentioning
confidence: 99%